PEMBENTUKAN HOLDING RUMAH SAKIT BADAN USAHA MILIK NEGARA (BUMN) STUDI KASUS PT. PERTAMINA BINA MEDIKA - INDONESIA HEALTHCARE CORPORATION - Asep Saifudin (Universitas Mercu Buana, 2018)
State-Owned Enterprises has long been a concern in improving the economy of a country. Therefore, efforts to improve the effeciences and effectiveness of the management of State-Owned Enterprises continue to be made to contribute greatly to the state. In some countries even formed Holding SOE Companies to manage SOE companies in order to compete with private companies. SOE companies in Indonesia besides managing the core business also has a hospital that was originally used to support the company's operations. However, in its development, the state-owned enterprises must be able to focus more on their management and can compete with other public and private hospitals. In order for the potential of SOE hospitals to grow and become a business corporation that is able to compete in national and international level, it is necessary to synergize through the establishment of state-owned holding company. PT. Pertamina Bina Medika was appointed by the Ministry of SOEs to be SOE Hospital Holding Company under the name Indonesia Healtcare Corporation.